Internet Gaming Disorder among Health Science Students of Kathmandu Valley - Maharjan, Luna; Adhikari, Anup; Pandit, Ramanand; Kharel, Indu (Morgan Journal of Interdisciplinary Research Studies, 2024)
Internet gaming disorder is characterized by persistent, unchecked gaming to the point where it interferes with other hobbies, everyday activities, and has harmful effects. Internet gaming is more common among younger people. This study aims to investigate the prevalence of risk of developing gaming disorder, and its related risk factors among health science students of Kathmandu, Nepal. A total of 422 public health students from Purbanchal University in Kathmandu filled out a Google form that was distributed by lecturers and representatives via email, Viber, and Messenger between January to March 2021. Data were gathered with administrative approval and individual agreement, and SPSS version 25 was used for analysis. The study indicated that the majority of students (84.8%) had a normal risk of acquiring internet gaming disorder, but a considerable minority (15.2%) were at risk. Although the majority of respondents who played games had appropriate gaming behaviour, a significant percentage of them were in danger. The finding showed a relationship between internet gaming disorder and variables including gender, semester, internet use, game features, game hours, and game money spent. Video games are widespread in current culture, yet a large minority suffers harmful consequences so policymakers are advised to create regulations that promote healthy gaming habits, such as prohibiting minor players and limiting access to online games at particular times.